2022
DOI: 10.1108/maj-03-2021-3061
|View full text |Cite
|
Sign up to set email alerts
|

CEO turnover and audit pricing: the role of media tone

Abstract: Purpose Prior research documents that chief executive officer (CEO) characteristics and succession planning affect audit fees. However, whether new CEOs’ media coverage influences audit fees remains unexplored. This study aims to fill this gap by examining whether auditors price media coverage of the new CEO. Design/methodology/approach The sample comprises 89 US listed firms with CEO turnover over the period 2012–2016, resulting in a total of 445 firm-year observations. Panel data models are used in the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…First, it enriches the existing business research by providing empirical evidence showing that busy CEOs are capable of managing the effectiveness of their business operations, which causes a significant increase in audit fees. In addition, our study contributes to the literature examining the association between director characteristics and audit fees in countries that have adopted the one-tier system (Cai and Li, 2022; Chao, 2022; Fernández-Méndez and Pathan, 2022). Specifically, our research offers a novel insight by investigating the impact of busy directors on audit fees in a two-tier system.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…First, it enriches the existing business research by providing empirical evidence showing that busy CEOs are capable of managing the effectiveness of their business operations, which causes a significant increase in audit fees. In addition, our study contributes to the literature examining the association between director characteristics and audit fees in countries that have adopted the one-tier system (Cai and Li, 2022; Chao, 2022; Fernández-Méndez and Pathan, 2022). Specifically, our research offers a novel insight by investigating the impact of busy directors on audit fees in a two-tier system.…”
Section: Introductionmentioning
confidence: 93%
“…Some previous studies have found that busier directors may increase the audit fee significantly (Fredriksson et al , 2020), whereas others have reported no relationship between busy directors and audit fees (Fernández Méndez et al , 2015). Other prior research has shown that different characteristics of the directors, such as female directors (Fernández-Méndez and Pathan, 2022), CEO turnover (Chao, 2022), tenure (Cai and Li, 2022) and directors’ compensation, are related to favorable audit fees.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation